Measurement of muscle food spoilage using fluorescence imaging - Wu, Binlin; Dahlberg, Kevin (Proceedings of SPIE, 2016)
Keywords: dept.phy

Introducing an analytical solution and an improved one-factor gaussian copula model for the pricing of heterogeneous CDOs - Gao, Xin; Wu, Binlin; Schäfer, Tobias (International Journal of Financial Engineering, 2017)
This paper introduced an analytical solution and improved one-factor Gaussian copula models to the pricing of tranches of a Collateralized debt obligations (CDO) portfolio. Prices of CDO tranches are calculated and compared using the analytical model and different one-factor Gaussian copula models including a two-category heterogeneous model and a completely heterogeneous model that uses individual rate parameter and correlation coefficient for each reference entity in a CDO portfolio. When correlation among reference entities is low, the price calculated from the analytical model matches very well with the one-factor Gaussian copula models. However, as the correlation among reference entities increases, prices calculated using both the analytical solution and the homogeneous or two-category one-factor Gaussian copula models significantly deviate from the completely heterogeneous one-factor Gaussian copula model. This result verifies our belief that uniform parameters cannot completely capture all the heterogeneities in a CDO portfolio. Completely heterogeneous one-factor Gaussian copula model using individual rate parameters and correlation coefficients for each reference entities provides more reliable and accurate prices for structured securities.
Keywords: dept.phy

Optical biopsy for prostate cancer diagnosis using fluorescence spectroscopy - Wu, Binlin; Gao, Xin; Smith, Jason (International Journal of High Speed Electronics and Systems, 2018)
Native fluorescence spectra are acquired from fresh normal and cancerous human prostate tissues. The fluorescence data are analyzed using an unsupervised machine learning algorithm such as non-negative matrix factorization. The nonnegative spectral components are retrieved and attributed to the native fluorophores such as collagen, reduced nicotinamide adenine dinucleotide (NADH), and flavin adenine dinucleotide (FAD) in tissue. The retrieved scores of the components are used to estimate the relative concentrations of the native fluorophores such as NADH and FAD and the redox ratio. A supervised machine learning algorithm such as support vector machine (SVM) is used to classify normal and cancerous tissue samples based on either the relative concentrations of NADH and FAD or the redox ratio alone. Various statistical measures such as sensitivity, specificity, and accuracy, along with the area under receiver operating characteristic (ROC) curve are used to show the classification performance. A cross validation method such as leave-one-out is used to further evaluate the predictive performance of the SVM classifier to avoid bias due to overfitting, and the accuracy was found to be 93.3%.
Keywords: Biopsy; Diseases; FAD; Factorization; Fluorescence; Fluorescence spectroscopy; Fluorophores; Learning algorithms; Learning systems; Machine learning; Matrix algebra; NADH; Nonnegative matrix factorization; Nucleotides; Optical biopsies; Optical emission spectroscopy; Prostate cancer; Prostate cancers; Redox ratio; Supervised learning; Support vector machines; Tissue; Urology; dept.phy; fluorescence spectroscopy; intrinsic tissue emission; machine learning; nonnegative matrix factorization; optical biopsy; peer-reviewed; redox ratio; support vector machine

A new method using multiphoton imaging and morphometric analysis for differentiating chromophobe renal cell carcinoma and oncocytoma kidney tumors - Wu, Binlin; Mukherjee, Sushmita; Jain, Manu (SPIE, 2016)
Distinguishing chromophobe renal cell carcinoma (chRCC) from oncocytoma on hematoxylin and eosin images may be difficult and require time-consuming ancillary procedures. Multiphoton microscopy (MPM), an optical imaging modality, was used to rapidly generate sub-cellular histological resolution images from formalin-fixed unstained tissue sections from chRCC and oncocytoma. Tissues were excited using 780nm wavelength and emission signals (including second harmonic generation and autofluorescence) were collected in different channels between 390 nm and 650 nm. Granular structure in the cell cytoplasm was observed in both chRCC and oncocytoma. Quantitative morphometric analysis was conducted to distinguish chRCC and oncocytoma. To perform the analysis, cytoplasm and granules in tumor cells were segmented from the images. Their area and fluorescence intensity were found in different channels. Multiple features were measured to quantify the morphological and fluorescence properties. Linear support vector machine (SVM) was used for classification. Re-substitution validation, cross validation and receiver operating characteristic (ROC) curve were implemented to evaluate the efficacy of the SVM classifier. A wrapper feature algorithm was used to select the optimal features which provided the best predictive performance in separating the two tissue types (classes). Statistical measures such as sensitivity, specificity, accuracy and area under curve (AUC) of ROC were calculated to evaluate the efficacy of the classification. Over 80% accuracy was achieved as the predictive performance. This method, if validated on a larger and more diverse sample set, may serve as an automated rapid diagnostic tool to differentiate between chRCC and oncocytoma. An advantage of such automated methods are that they are free from investigator bias and variability. Copyright © 2016 SPIE.
Keywords: Artificial intelligence; Autofluorescence; Cancer diagnosis; Cells; Classification (of information); Computer aided diagnosis; Cytology; Diagnosis; Diseases; Fluorescence; Harmonic generation; Imaging techniques; Kidney cancer; Learning algorithms; Learning systems; Morphometric analysis; Multi-photon microscopy; Multiphoton microscopy; Nonlinear optics; Support vector machines; Tissue; Tumors; autofluorescence; cancer diagnosis; classification; dept.phy; imaging; kidney cancer; machine learning; morphometric analysis

Time reversal optical tomography: Detecting and locating tumors in an ex vivo model human breast - Wu, Binlin; Alrubaiee, M.; Gayen, S. K. (Optics and Laser Technology, 2016)
Time reversal optical tomography (TROT), a recently introduced diffuse optical imaging approach, is used to detect, locate, and obtain cross-section images of tumors inside a "model human breast." The model cancerous breast is assembled as a semi-cylindrical slab of uniform thickness using ex vivo human breast tissues with two pieces of tumors embedded in it. The experimental arrangement used a 750-nm light beam from a Ti:sapphire laser to illuminate an end face (source plane) of the sample in a multi-source probing scheme. A multi-detector signal acquisition scheme measured transmitted light intensity distribution on the other end face (detector plane). The perturbations in light intensity distribution in the detector plane were analyzed using TROT to obtain locations of the tumor pieces in three dimensions and estimate their cross sections. The estimated locations and dimensions of targets are in good agreement with the results of a corroborating magnetic resonance imaging experiment. © 2015 Elsevier Ltd. All rights reserved.
Keywords: Biological tissues; Breast Cancer; Breast cancer; Histology; Image reconstruction; Infrared devices; Infrared imaging; Inverse image reconstruction; Light propagation; Light propagation in biological tissues; Location; Magnetic resonance imaging; Medical imaging; Near-infrared imaging; Optical tomography; Sapphire; Signal processing; Thermography (imaging); Time reversal; Tissue; Tumors; dept.phy

Optical biopsy using fluorescence spectroscopy for prostate cancer diagnosis - Wu, Binlin; Gao, Xin; Smith, Jason; Bailin, Jacob (Therapeutics and Diagnostics in Urology: Lasers, Robotics, Minimally Invasive, and Advanced Biomedical Devices, 2017)
Native fluorescence spectra are acquired from fresh normal and cancerous human prostate tissues. The fluorescence data are analyzed using a multivariate analysis algorithm such as non-negative matrix factorization. The nonnegative spectral components are retrieved and attributed to the native fluorophores such as collagen, reduced nicotinamide adenine dinucleotide (NADH), and flavin adenine dinucleotide (FAD) in tissue. The retrieved weights of the components, e.g. NADH and FAD are used to estimate the relative concentrations of the native fluorophores and the redox ratio. A machine learning algorithm such as support vector machine (SVM) is used for classification to distinguish normal and cancerous tissue samples based on either the relative concentrations of NADH and FAD or the redox ratio alone. The classification performance is shown based on statistical measures such as sensitivity, specificity, and accuracy, along with the area under receiver operating characteristic (ROC) curve. A cross validation method such as leave-one-out is used to evaluate the predictive performance of the SVM classifier to avoid bias due to overfitting.
Keywords: Artificial intelligence; Biopsy; Cross validation; Diseases; Factorization; Fluorescence; Fluorescence spectroscopy; Fluorophores; Learning algorithms; Learning systems; Matrix algebra; Multivariant analysis; Nonnegative matrix factorization; Nucleotides; Optical biopsies; Prostate cancers; Redox ratio; Robotics; Support vector machines; Tissue; Urology; cross validation; dept.phy; fluorescence spectroscopy; machine learning; nonnegative matrix factorization; optical biopsy; prostate cancer; redox ratio; support vector machine

Characterization of ZnO and Fe doped ZnO nanoparticles using fluorescence spectroscopy - Singhal, Rahul; Fernando, Mihiri; LeMaire, Peter K.; Wu, Binlin (Oxide-based Materials and Devices X, 2019)
In this study, nanoparticles of pure zinc oxide (ZnO) and ZnO doped with iron of various doping concentrations (Zn1- xFexO) are analyzed using fluorescence spectroscopy. Excitation and emission spectra using various operating wavelengths were collected. Individual spectra and excitation emission matrix were analyzed. Various peaks including strong ultraviolet (UV) emission peaks and strong blue emission peaks that are corresponding to the near-band-edge emission (NBE) and defect emission (DE) peaks were studied based on the peak intensities, peak wavelengths, and NBE peak to defect peak ratios. The Zn1-xFexO materials were also analyzed using X-ray diffraction and optical absorption spectroscopy. The variation in the band gap energy and in the NBE emission energy with dopant concentration was analyzed. A red-shift was observed with the NBE emission peak. The NBE to DE ratio initially increases from pure ZnO to Zn0.97Fe0.03O and then decreases as the dopant concentration increases.
Keywords: Absorption spectroscopy; Band Gap; Band-edge emission (NBE); Band-edge emissions; Defect emission; Defect emission (DE); Defects; Dopant concentrations; Doping concentration; Emission spectroscopy; Energy gap; Excitation and emission spectra; Excitation emission matrices; Fluorescence; Fluorescence spectroscopy; II-VI semiconductors; Iron; Laser radiation; Light absorption; Nanoparticles; Near band edge emissions; Red Shift; Semiconductor doping; X ray diffraction; X-ray diffraction; Zinc oxide; Zinc oxide (ZnO); ZnO nanoparticles; dept.phy

Rapid measurement of meat spoilage using fluorescence spectroscopy - Wu, Binlin; Dahlberg, Kevin; Gao, Xin; Smith, Jason; Bailin, Jacob (Imaging, Manipulation, and Analysis of Biomolecules, Cells, and Tissues XV, 2017)
Food spoilage is mainly caused by microorganisms, such as bacteria. In this study, we measure the autofluorescence in meat samples longitudinally over a week in an attempt to develop a method to rapidly detect meat spoilage using fluorescence spectroscopy. Meat food is a biological tissue, which contains intrinsic fluorophores, such as tryptophan, collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) etc. As meat spoils, it undergoes various morphological and chemical changes. The concentrations of the native fluorophores present in a sample may change. In particular, the changes in NADH and FAD are associated with microbial metabolism, which is the most important process of the bacteria in food spoilage. Such changes may be revealed by fluorescence spectroscopy and used to indicate the status of meat spoilage. Therefore, such native fluorophores may be unique, reliable and nonsubjective indicators for detection of spoiled meat. The results of the study show that the relative concentrations of all above fluorophores change as the meat samples kept in room temperature (~19° C) spoil. The changes become more rapidly after about two days. For the meat samples kept in a freezer (~-12° C), the changes are much less or even unnoticeable over a-week-long storage.
Keywords: Amino acids; Bacteria; Biological tissues; Biomolecules; Collagen; Flavin adenine dinucleotide; Fluorescence; Fluorescence spectroscopy; Fluorophores; Food microbiology; Histology; Meat food; Meats; Metabolism; Microbial metabolism; Molecular biology; NADH; Nicotinamide adenine dinucleotides; Nucleotides; Physiology; Rapid measurement; Relative concentration; Spectrum analysis; Spoilage; Tissue; Tryptophan; dept.phy

A Rapid Method Based on Fluorescence Spectroscopy for Meat Spoilage Detection - Wu, Binlin; Dahlberg, Kevin; Gao, Xin; Smith, Jason; Bailin, Jacob (International Journal of High Speed Electronics and Systems, 2018)
Food spoilage is mainly caused by microorganisms, such as bacteria. In this study, we measure the autofluorescence in meat samples longitudinally over a week in an attempt to develop a method to rapidly detect meat spoilage using fluorescence spectroscopy. Meat food is a biological tissue, which contains intrinsic fluorophores, such as tryptophan, collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) etc. As meat spoils, it undergoes various morphological and chemical changes. The concentrations of the native fluorophores present in a sample may change. In particular, the changes in NADH and FAD are associated with microbial metabolism, which is the most important process of the bacteria in food spoilage. Such changes may be revealed by fluorescence spectroscopy and used to indicate the status of meat spoilage. Therefore, such native fluorophores may be unique, reliable and non-subjective indicators for detection of spoiled meat. The results of the study show that the relative concentrations of all above fluorophores change as the meat samples kept in room temperature (~19°C) spoil. The changes become more rapidly after about two days. For the meat samples kept in a freezer (~ -12°C), the changes are much less or even unnoticeable over a-week-long storage.
Keywords: Amino acids; Autofluorescence; Bacteria; Biological tissues; Collagen; Flavin adenine dinucleotide; Fluorescence; Fluorescence spectroscopy; Fluorophores; Food microbiology; Meats; Metabolism; Microbial metabolism; NADH; Nicotinamide adenine dinucleotides; Nucleotides; Relative concentration; Spoilage; bacteria; collagen; dept.phy; fluorescence spectroscopy; meat food; microbial metabolism; peer-reviewed; tryptophan

Distinguish chromophobe renal cell carcinoma and renal oncocytoma based on analysis of multiphoton microscopic images using convolutional neural network - Icaza, Michael; Judd, Nicolas; Jain, Manu; Mukherjee, Sushmita; Wu, Binlin (Optical Biopsy XVII: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2019)
Convolutional neural networks (CNN) are a class of machine learning model that are especially well suited for imagebased tasks. In this study, we design and train a CNN on tissue samples imaged using Multi-Photon Microscopy (MPM) and show that the model can distinguish between chromophobe renal cell carcinoma (chRCC) and oncocytoma. We demonstrate the method to train a model using simple max-pooling vote fusion, and use the model to highlight regions of the input that cause a positive classification. The model can be tuned for higher sensitivity at the cost of specificity with a constant threshold and little impact to accuracy overall. Several numerical experiments were run to measure the model’s accuracy on both image and patient level analysis. Our models were designed with a dropout parameter that biases the model towards higher sensitivity or specificity. Our best performance model, as measured by area under the receiver operating characteristic curve (AUC of ROC, or AUROC) on patient level classification, is measured with a 94% AUROC and 88% accuracy, along with 100% sensitivity and 75% specificity.
Keywords: Biopsy; Chromophobe renal cell carcinoma; Convolution; Convolutional neural network; Convolutional neural network (CNN); Deep learning; Deep neural networks; Harmonic generation; Image analysis; Kidney tumor; Learning algorithms; Malignancy; Multiphoton microscopy; Multiphoton microscopy (MPM); Neural networks; Nonlinear optics; Renal cell carcinoma; Renal oncocytoma; Second harmonic generation (SHG); dept.phy

Exploring multiphoton microscopy as a novel tool to differentiate chromophobe renal cell carcinoma from oncocytoma in fixed tissue sections - Jain, Manu; Robinson, Brian D.; Wu, Binlin; Khani, Francesca; Mukherjee, Sushmita (Archives of Pathology & Laboratory Medicine, 2018)
Context.-Distinguishing chromophobe renal cell carcinoma (chRCC), especially in the presence of eosinophilic cytoplasm, from oncocytoma on hematoxylin-eosin can be difficult and often requires time-consuming ancillary procedures that ultimately may not be informative. Objective.-To explore the potential of multiphoton microscopy (MPM) as an alternative and rapid diagnostic tool in differentiating oncocytoma from chRCC at subcellular resolution without tissue processing. Design.-Unstained, deparaffinized tissue sections from 27 tumors (oncocytoma [n = 12], chRCC [n = 12], eosinophilic variant of chRCC [n = 1], and atypical oncocytic renal neoplasm [n = 2]) were imaged with MPM. Morphologic evaluation and automated quantitative morphometric analysis were conducted to distinguish between chRCC and oncocytoma. Results.-The typical cases of oncocytomas (12 of 12) and chRCC (12 of 12) could be readily differentiated on MPM based on the morphologic features similar to hematoxylin-eosin. The most striking MPM signature of both of the tumors was the presence of autofluorescent intracytoplasmic granules, which are not seen on hematoxylin-eosin-stained slides. Although we saw these granules in both types of tumors, they appeared distinct, based on their size, shape, cytoplasmic distribution, and autofluorescence wavelengths, and were valuable in arriving at a definitive diagnosis. For oncocytomas and chRCC, high diagnostic accuracies of 100% and 83.3% were achieved on blinded MPM and morphometric analysis, respectively. Conclusions.-To the best of our knowledge, this is the first demonstration of MPM to distinguish chRCC from oncocytoma in fixed tissues. Our study was limited by small sample size and only a few variants of oncocytic tumors. Prospective studies are warranted to assess the utility of MPM as a diagnostic aid in oncocytic renal tumors. © Copyright 2018 College of American Pathologists.
Keywords: Adenoma, Oxyphilic; Carcinoma, Renal Cell; Diagnosis, Differential; Humans; Kidney Neoplasms; Microscopy, Fluorescence, Multiphoton; Tissue Fixation; dept.phy; differential diagnosis; human; kidney tumor; multiphoton microscopy; oncocytoma; pathology; peer-reviewed; procedures; renal cell carcinoma; tissue fixation

Characterization and discrimination of human breast cancer and normal breast tissues using resonance Raman spectroscopy - Wu, Binlin; Smith, Jason; Zhang, Lin; Gao, Xin; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
Worldwide breast cancer incidence has increased by more than twenty percent in the past decade. It is also known that in that time, mortality due to the affliction has increased by fourteen percent. Using optical-based diagnostic techniques, such as Raman spectroscopy, has been explored in order to increase diagnostic accuracy in a more objective way along with significantly decreasing diagnostic wait-times. In this study, Raman spectroscopy with 532-nm excitation was used in order to incite resonance effects to enhance Stokes Raman scattering from unique biomolecular vibrational modes. Seventy-two Raman spectra (41 cancerous, 31 normal) were collected from nine breast tissue samples by performing a ten-spectra average using a 500-ms acquisition time at each acquisition location. The raw spectral data was subsequently prepared for analysis with background correction and normalization. The spectral data in the Raman Shift range of 750- 2000 cm-1 was used for analysis since the detector has highest sensitivity around in this range. The matrix decomposition technique nonnegative matrix factorization (NMF) was then performed on this processed data. The resulting leave-oneout cross-validation using two selective feature components resulted in sensitivity, specificity and accuracy of 92.6%, 100% and 96.0% respectively. The performance of NMF was also compared to that using principal component analysis (PCA), and NMF was shown be to be superior to PCA in this study. This study shows that coupling the resonance Raman spectroscopy technique with subsequent NMF decomposition method shows potential for high characterization accuracy in breast cancer detection.
Keywords: Background correction; Biopsy; Breast Cancer; Breast cancer; Breast cancer detection; Cancer diagnosis; Couplings; Decomposition methods; Diagnostic techniques; Diseases; Factorization; Learning systems; Machine learning; Matrix algebra; Molecular optical pathology; Nonnegative matrix factorization; Principal component analysis; Principal component analysis (PCA); Raman scattering; Raman spectroscopy; Resonance; Resonance Raman spectroscopy; Spectrum analysis; Support vector machine; Support vector machines; Tissue; dept.phy

Visible resonance raman spectroscopy in human brain tissues - Zhou, Yan; Liu, Cheng-hui; Zhu, Ke; Wu, Binlin; Yu, Xinguang; Alfano, Robert R. (Neurophotonics and Biomedical Spectroscopy, 2019)
This chapter first reviews the research and applications of nonresonance and resonance Raman spectroscopy for analysis of human brain normal and abnormal tissues. Next, special emphasis is made on our recent achievements of visible resonance Raman (VRR) technique in primary human brain tumor disease investigation and diagnosis. Visible resonance Raman (VRR) spectroscopy technique uses excitation of visible light (532 nm) to evaluate the resonant and nonresonant molecular vibrational modes in biological tissues. The VRR signal intensities are enhanced by two to three orders of magnitude for faster use in medical applications in quasi real time. VRR opens up a new stainless “molecular optics based histopathology” diagnosis approach. © 2019 Elsevier Ltd. All rights reserved.
Keywords: Brain cancer margin assessment; Glioblastoma multiforme (GBM); Glioblastoma multiforme (gbm); Gliomas; Meninges; Optical biopsy; Visible resonance Raman (VRR) spectroscopy; Visible resonance raman (vrr) spectroscopy; Wavelength 532 nm; Wavelength 532nm; dept.phy

Quantitative characterization for identification of brain cancer surgical margin using resonance Raman spectroscopy - Zhou, Yan; Liu, Chenghui; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhang, Chunyuan; Alfano, R R (OSA - The Optical Society, 2017)
A new criterion was developed to characterize brain tissue using resonance Raman spectroscopy, by which, negative margins of cancer can be differentiated from normal tissues. This method may help a surgeon better decide surgical margins. © OSA 2017.
Keywords: Brain cancer; Brain tissue; Diseases; Normal tissue; Quantitative characterization; Raman spectroscopy; Resonance Raman spectroscopy; Surgery; Tissue; dept.phy

A component‐by‐component characterisation of high‐risk atherosclerotic plaques by multiphoton microscopic imaging - Jain, Manu; Wu, Binlin; Pisapia, David J; Salvatore, Steven P; Mukherjee, Sushmita; Narula, Navneet; Mukherjee, Sushmita; Narula, Navneet (Journal of Microscopy, 2017)
Aims: Atherosclerotic plaques vulnerable to rupture are almost always inflamed, and carry a large lipid core covered by a thin fibrous cap. The other components may include neovascularisation, intraplaque haemorrhage and spotty calcification. In contrast, stable plaques are characterised by a predominance of smooth muscle cells and collagen, and lipid core is usually deep seated or absent. This study is a proof of principle experiment to evaluate the feasibility of multiphoton microscopy (MPM) to identify aforementioned plaque components. Methods and Results: MPM is a nonlinear optical technique that allows imaging based on intrinsic tissue signals including autofluorescence and higher-order scattering. In our study, MPM imaging was performed on morphologically diverse aortic and coronary artery plaques obtained during autopsy. Various histologically verified plaque components including macrophages, cholesterol crystals, haemorrhage, collagen and calcification were recognised by MPM. Conclusions: Recognition of the distinct signatures of various plaque components suggests that MPM has the potential to offer next-generation characterisation of atherosclerotic plaques. The higher lateral resolution (comparable to histology) images generated by MPM for identifying plaque components might complement larger field of view and greater imaging depth currently available with optical coherence tomography imaging. As the next step MPM would need to be evaluated for intact vessel imaging ex vivo and in vivo. © 2017 The Authors Journal of Microscopy © 2017 Royal Microscopical Society
Keywords: Aorta; Article; Atherosclerotic plaque; Calcinosis; Cholesterol; Collagen; Coronary Vessels; Hemorrhage; Humans; Image Processing, Computer-Assisted; Macrophages; Nonlinear Optical Microscopy; Plaque, Atherosclerotic; aorta; atherosclerotic plaque; autofluorescence; autopsy; bleeding; calcinosis; cholesterol; clinical article; collagen; coronary artery; coronary artery calcification; coronary blood vessel; dept.phy; ex vivo; ex vivo study; feasibility study; histopathology; human; human tissue; image processing; immunology; macrophage; macrophages; multiphoton microscopy; nonlinear optical microscopy; pathology; priority journal; procedures

A pilot study for distinguishing chromophobe renal cell carcinoma and oncocytoma using second harmonic generation imaging and convolutional neural network analysis of collagen fibrillar structure - Wu, Binlin; Judd, Nicolas; Smith, Jason; Icaza, Michael; Mukherjee, Sushmita; Jain, Manu; Gallagher, Ryan M; Szeligowski, Richard V (2018)
A clear distinction between oncocytoma and chromophobe renal cell carcinoma (chRCC) is critically important for clinical management of patients. But it may often be difficult to distinguish the two entities based on hematoxylin and eosin (H and E) stained sections alone. In this study, second harmonic generation (SHG) signals which are very specific to collagen were used to image collagen fibril structure. We conduct a pilot study to develop a new diagnostic method based on the analysis of collagen associated with kidney tumors using convolutional neural networks (CNNs). CNNs comprise a type of machine learning process well-suited for drawing information out of images. This study examines a CNN model's ability to differentiate between oncocytoma (benign), and chRCC (malignant) kidney tumor images acquired with second harmonic generation (SHG), which is very specific for collagen matrix. To the best of our knowledge, this is the first study that attempts to distinguish the two entities based on their collagen structure. The model developed from this study demonstrated an overall classification accuracy of 68.7% with a specificity of 66.3% and sensitivity of 74.6%. While these results reflect an ability to classify the kidney tumors better than chance, further studies will be carried out to (a) better realize the tumor classification potential of this method with a larger sample size and (b) combining SHG with two-photon excited intrinsic fluorescence signal to achieve better classification. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
Keywords: Biomedical signal processing; Biopsy; Chromophobe renal cell carcinoma; Classification accuracy; Collagen; Convolution; Convolutional Neural Networks (CNN); Convolutional neural network; Convolutional neural networks (CNN); Fluorescence; Harmonic analysis; Harmonic generation; Intrinsic fluorescence signals; Kidney tumor; Learning systems; Machine learning; Multiphoton microscopy; Multiphoton microscopy (MPM); Multiphoton processes; Neural networks; Nonlinear optics; Patient monitoring; Renal cell carcinoma; Renal oncocytoma; Second harmonic generation; Tumor classification; Tumors; dept.phy

Diagnosis of glioma brain cancer using visible resonance Raman spectroscopy - Zhou, Yan; Wu, Binlin; Liu, Chenghui; Yu, Xinguang; Cheng, Gangge; Wang, Kai; Zhang, Chunyuan; Shi, Lingyan; Alfano, R R (OSA, 2018)
Resonance Raman spectroscopy using 532nm excitation was used to distinguish normal brain tissue from different grades of glioma tissues. Principal component analysis was used to analyze the spectral data and achieved high accuracy. © 2018 The Author(s).
Keywords: Brain cancer; Brain tissue; Different grades; Glioma tissues; High-accuracy; Principal component analysis; Raman spectroscopy; Resonance Raman spectroscopy; Spectral data; Tumors; dept.phy

Resonance raman of BCC and normal skin - Liu, Cheng-hui; Sriramoju, Vidyasagar; Boydston-White, Susie; Wu, Binlin; Zhang, Chunyuan; Pei, Zhe; Sordillo, Laura; M.d, Hugh Beckman; Alfano, Robert R. (Optical Biopsy XV: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2017)
The Resonance Raman (RR) spectra of basal cell carcinoma (BCC) and normal human skin tissues were analyzed using 532nm laser excitation. RR spectral differences in vibrational fingerprints revealed skin normal and cancerous states tissues. The standard diagnosis criterion for BCC tissues are created by native RR biomarkers and its changes at peak intensity. The diagnostic algorithms for the classification of BCC and normal were generated based on SVM classifier and PCA statistical method. These statistical methods were used to analyze the RR spectral data collected from skin tissues, yielding a diagnostic sensitivity of 98.7% and specificity of 79% compared with pathological reports.
Keywords: Basal cell carcinoma; Basel cell carcinoma (BCC); Biopsy; Cell carcinoma; Diagnostic algorithms; Histology; Human skin; Human skin tissues; Laser excitation; Principal component analysis; Principal component analysis (PCA); Resonance; Resonance Raman spectra; Resonance Raman spectroscopy; Skin cancer; Skin cancers; Spectral differences; Statistical methods; Support vector machine (SVM); Support vector machines; Tissue; Tissue engineering; dept.phy

Assessment of basal cell carcinoma from normal human skin tissues using Resonance Raman spectroscopy - Liu, Chenghui; Wu, Binlin; Sordillo, Laura A; Boydstonwhite, Susie; Sriramoju, Vidyasagar; Zhang, Chunyuan; Beckman, Hugh; Zhang, Lin; Pei, Zhe; Shi, Lingyan; Alfano, R R (OSA - The Optical Society, 2018)
VRR spectroscopy was used for BCC and normal skin tissues with 532nm excitation. The spectra showed significant changes in collagen, carotenoids and lipids. These enhanced fingerprints demonstrate a potential use as label-free pathology method. © 2018 The Author(s).
Keywords: Basal cell carcinoma; Histology; Human skin; Label free; Normal skin; Resonance Raman spectroscopy; Tissue; dept.phy

Resonance raman imaging for detecting and monitoring molecular pathological changes in human brain tumors related to Warburg effect - Zhou, Yan; Liu, Cheng-hui; Zhu, Ke; Zhang, Chunyuan; Yang, Yang; Yu, Xinguang; Hu, Hailong; Cheng, Gangge; Wu, Binlin; Shi, Lingyan; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
The goal of the research is to determine the prognostic molecular pathological changes in components and composition, for human brain glioma gradings in comparison with normal tissues in three-dimensional Raman imaging profiles by visible Resonance Raman (VRR) imaging. VRR images from twenty-five specimens including three healthy tissues, one normal control, and twenty-one glioma tissues of grades II, II-III and III-IV with histology examination were measured and investigated using WITec300R confocal micro Raman imaging system with laser excitation of 532nm. Two-dimensional RR spectral mappings performed in 20μm x 20μm generated 400 images which integrated the intensity of the specific biochemical bonds as the third dimension. The three-dimension (3D) map demonstrated the spatial distributions of three selected sets of RR spectra of molecular biomarkers, and revealed significant differences in the spectra between normal and glioma tissues of different grades due to the composition changes in key molimageecules. These RR molecular spectral fingerprints have displayed: a clear enhancement of RR vibrational modes at 1129-1131cm-1 and 2934cm-1 which are supposed to be arising from lipoproteins; evident decreased RR vibrational modes at 1442cm-1 and 2854cm-1 which are from saturated fatty acids bonds in all-grades of glioma brain tissues compared with normal tissues; and the enhanced RR spectral modes of 1129 cm-1 and 2938cm-1 which suggest contribution from lactate. These findings may provide a novel proof for anaerobic glycolysis metabolic process in brain glioma cancer tissues that has been explained by Warburg effects.
Keywords: 2-d imaging; 2D imaging; Biopsy; Brain; Gliomas; Histology; Human Brain Tissues; Human brain; Laser excitation; Molecular imaging; Resonance; Resonance Raman; Saturated fatty acids; Tumors; Visible resonance Raman (VRR); Warburg effect; Warburg effects; dept.phy

Combined spatial frequency spectroscopy analysis with visible resonance Raman for optical biopsy of human brain metastases of lung cancers - Zhou, Yan; Liu, Cheng-Hui; Pu, Yang; Wu, Binlin; Nguyen, Thien An; Cheng, Gangge; Zhou, Lixin; Zhu, Ke; Chen, Jun; Li, Qingbo; Alfano, Robert R. (Journal of Innovative Optical Health Sciences, 2019)
The purpose of this study is to examine optical spatial frequency spectroscopy analysis (SFSA) combined with visible resonance Raman (VRR) spectroscopic method, for the first time, to discriminate human brain metastases of lung cancers adenocarcinoma (ADC) and squamous cell carcinoma (SCC) from normal tissues. A total of 31 label-free micrographic images of three types of brain tissues were obtained using a confocal micro-Raman spectroscopic system. VRR spectra of the corresponding samples were synchronously collected using excitation wavelength of 532[Formula: see text]nm from the same sites of the tissues. Using SFSA method, the difference in the randomness of spatial frequency structures in the micrograph images was analyzed using Gaussian function fitting. The standard deviations, [Formula: see text] calculated from the spatial frequencies of the micrograph images were then analyzed using support vector machine (SVM) classifier. The key VRR biomolecular fingerprints of carotenoids, tryptophan, amide II, lipids and proteins (methylene/methyl groups) were also analyzed using SVM classifier. All three types of brain tissues were identified with high accuracy in the two approaches with high correlation. The results show that SFSA–VRR can potentially be a dual-modal method to provide new criteria for identifying the three types of human brain tissues, which are on-site, real-time and label-free and may improve the accuracy of brain biopsy.
Keywords: Amides; Amino acids; Article; Biopsy; Brain; Diseases; Histology; Human brain; Image analysis; Metastatic lung cancer; Pathology; Raman spectrometry; Resonance; Resonance Raman; Spatial frequency; Spatial frequency spectroscopy analysis (SFSA); Spatial variables measurement; Spectroscopic analysis; Spectrum analysis; Support vector machines; Tissue; accuracy; amide; brain metastasis; brain tissue; cancer classification; carbene; carotenoid; controlled study; dept.phy; diagnostic test accuracy study; excitation; fatty acid; high density lipoprotein; histopathology; human; human brain; human tissue; lipid; low density lipoprotein; lung adenocarcinoma; metastatic lung cancer; methyl group; molecular imaging; peer-reviewed; photomicrograph image; sensitivity and specificity; spatial frequency spectroscopy analysis; spectroscopy; squamous cell lung carcinoma; support vector machine; support vector machine (SVM); tryptophan; visible resonance Raman (VRR); visible resonance Raman spectroscopy

A pilot study for distinguishing basal cell carcinoma from normal human skin tissues using visible resonance Raman spectroscopy - Liu, Cheng-hui; Wu, Binlin; Sordillo, Laura A.; Boydston-White, Susie; Sriramoju, Vidyasagar; Zhang, Chunyuan; Beckman, Hugh; Zhang, Lin; Pei, Zhe; Shi, Lingyan; Alfano, Robert R. (Journal of Cancer Metastasis and Treatment, 2019)
Keywords: dept.phy; peer-reviewed

Statistical analysis and machine learning algorithms for optical biopsy - Wu, Binlin; Liu, Cheng-hui; Boydston-White, Susie; Beckman, Hugh; Sriramoju, Vidyasagar; Sordillo, Laura; Zhang, Chunyuan; Zhang, Lin; Shi, Lingyan; Smith, Jason; Bailin, Jacob; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
Analyzing spectral or imaging data collected with various optical biopsy methods is often times difficult due to the complexity of the biological basis. Robust methods that can utilize the spectral or imaging data and detect the characteristic spectral or spatial signatures for different types of tissue is challenging but highly desired. In this study, we used various machine learning algorithms to analyze a spectral dataset acquired from human skin normal and cancerous tissue samples using resonance Raman spectroscopy with 532nm excitation. The algorithms including principal component analysis, nonnegative matrix factorization, and autoencoder artificial neural network are used to reduce dimension of the dataset and detect features. A support vector machine with a linear kernel is used to classify the normal tissue and cancerous tissue samples. The efficacies of the methods are compared.
Keywords: Artificial neural network; Biological basis; Biopsy; Cancer diagnosis; Cancerous tissues; Factorization; Learning algorithms; Learning systems; Least squares approximations; Machine learning; Matrix algebra; Neural networks; Nonnegative matrix factorization; Optical biopsies; Optical biopsy; Partial least square (PLS); Partial least squares; Principal component analysis; Resonance Raman spectroscopy; Spatial signature; Support vector machine; Support vector machines; Tissue; Tissue engineering; dept.phy

Invited Article: Molecular biomarkers characterization for human brain glioma grading using visible resonance Raman spectroscopy - Zhou, Yan; Liu, Cheng-hui; Wu, Binlin; Zhang, Chunyuan; Yu, Xinguang; Cheng, Gangge; Chen, Hong; Li, Shenglin; Liang, Qijun; Zhang, Mingqian; Zhu, Ke; Shi, Lingyan; et al. (APL Photonics, 2018)
The accurate identification of the human brain tumor boundary and the complete resection of the tumor are two essential factors for the removal of the glioma tumor in brain surgery. We present a visible resonance Raman (VRR) spectroscopy technique for differentiating the brain tumor margin and glioma grading. Eighty-seven VRR spectra from twenty-one human brain specimens of four types of brain tissues, including the control, glioma grade II, III, and IV tissues, were observed. This study focuses on observing the characteristics of new biomarkers and their changes in the four types of brain tissue. We found that two new RR peaks at 1129 cm-1 and 1338 cm-1 associated with molecular vibrational bonds in four types of brain tissues are significantly different in peak intensities of VRR spectra. These two resonance enhanced peaks may arise from lactic acid/phosphatidic acid and adenosine triphosphate (ATP)/nicotinamide adenine dinucleotide, respectively. We found that lactic acid and ATP concentrations vary with glioma gratings. The higher the grade of malignancy, the more the increase in lactic acid and ATP concentrations. These two RR peaks may be considered as new molecular biomarkers and used to evaluate glioma grades and identify the margin of gliomas from the control tissues. The metabolic process of lactic acid and ATP in glioma cells based on the VRR spectral changes may reveal the Warburg hypothesis. © 2018 Author(s).
Keywords: Adenosinetriphosphate; Biomarkers; Brain; Control tissues; Grading; Histology; Human brain tumors; Lactic acid; Metabolic process; Molecular biomarker; Resonance; Resonance Raman; Resonance Raman spectroscopy; Resonance enhanced; Spectral change; Tumors; dept.phy; peer-reviewed

Optical biopsy identification and grading of gliomas using label-free visible resonance Raman spectroscopy. - Zhou, Yan; Liu, Cheng-Hui; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhu, Ke; Wang, Kai; Zhang, Chunyuan; Zhao, Mingyue; Zong, Rui; Zhang, Lin; Shi, Lingyan; et al. (Journal of biomedical optics, 2019)
Glioma is one of the most refractory types of brain tumor. Accurate tumor boundary identification and complete resection of the tumor are essential for glioma removal during brain surgery. We present a method based on visible resonance Raman (VRR) spectroscopy to identify glioma margins and grades. A set of diagnostic spectral biomarkers features are presented based on tissue composition changes revealed by VRR. The Raman spectra include molecular vibrational fingerprints of carotenoids, tryptophan, amide I/II/III, proteins, and lipids. These basic in situ spectral biomarkers are used to identify the tissue from the interface between brain cancer and normal tissue and to evaluate glioma grades. The VRR spectra are also analyzed using principal component analysis for dimension reduction and feature detection and support vector machine for classification. The cross-validated sensitivity, specificity, and accuracy are found to be 100%, 96.3%, and 99.6% to distinguish glioma tissues from normal brain tissues, respectively. The area under the receiver operating characteristic curve for the classification is about 1.0. The accuracies to distinguish normal, low grade (grades I and II), and high grade (grades III and IV) gliomas are found to be 96.3%, 53.7%, and 84.1% for the three groups, respectively, along with a total accuracy of 75.1%. A set of criteria for differentiating normal human brain tissues from normal control tissues is proposed and used to identify brain cancer margins, yielding a diagnostic sensitivity of 100% and specificity of 71%. Our study demonstrates the potential of VRR as a label-free optical molecular histopathology method used for in situ boundary line judgment for brain surgery in the margins.
Keywords: *Biomarkers, Tumor/me [Metabolism]; *Brain Neoplasms/me [Metabolism]; *Brain Neoplasms/pa [Pathology]; *Glioma/me [Metabolism]; *Glioma/pa [Pathology]; *Spectrum Analysis, Raman/mt [Methods]; Amides; Amino acids; Biomarkers; Biomarkers, Tumor; Biomarkers, Tumor/ch [Chemistry]; Biopsy; Brain; Brain Neoplasms; Brain Neoplasms/su [Surgery]; Brain/me [Metabolism]; Brain/pa [Pathology]; Brain/su [Surgery]; Cancer grades; Cancer margins; Carotenoids; Carotenoids/me [Metabolism]; Diseases; Glioblastoma; Glioblastomas; Glioma; Glioma/su [Surgery]; Gliomas; Grading; Histology; Histopathology; Humans; Label free; Label-free; Lipid Metabolism; Margins of Excision; Neoplasm Grading; Nerve Tissue Proteins; Nerve Tissue Proteins/ch [Chemistry]; Nerve Tissue Proteins/me [Metabolism]; Optical Phenomena; Optical biopsies; Optical biopsy; Pigments; Principal Component Analysis; Principal component analysis; Protein Structure, Secondary; Raman spectrometry; Resonance; Resonance Raman; Spectrum Analysis, Raman; Support Vector Machine; Support vector machines; Surgery; Tryptophan; Tryptophan/me [Metabolism]; Tumors; brain; brain tumor; cancer grading; carotenoid; chemistry; dept.phy; glioma; human; light related phenomena; lipid metabolism; metabolism; nerve protein; pathology; peer-reviewed; principal component analysis; procedures; protein secondary structure; support vector machine; surgical margin; tryptophan; tumor marker

Visible resonance Raman spectroscopy detect key molecular biomarker vibrations to characterize for human brain gliomas - Zhou, Yan; Liu, Cheng-hui; Wu, Binlin; Yu, Xinguang; Gangge Cheng; Zhang, Chunyuan; Chen, Hong; Li, Shenglin; Zong, Rui; Liang, Qijun; Zhang, Ce; Zhang, Mingqian; et al. (Biomedical Imaging and Sensing Conference, 2018)
Visible resonant Raman (VRR) spectroscopy provides an effective way to enhance Raman signal from particular bonds associated with key molecules due to changes on molecular level. This paper reports on the VRR use for detection of human brain the control and gliomas of three grades. From the RR spectra additional two molecular vibrational biomarkers at 1129cm-1 and 1338cm-1, for the four types of brain tissues are significantly different in intensity. The new RR spectral peaks can be used as molecular biomarkers to evaluate glioma grades and identify the margin of gliomas from the controls. The metabolic process of glioma cells based on the RR spectral changes may reveal the Warburg hypothesis.
Keywords: 532nm; Biomarkers; Brain; Human brain tumors; Medical imaging; Raman probe; Raman spectroscopy; Resonance Raman; Tumors; Visible resonance Raman (VRR); confical Raman probe; dept.phy; gliomas; human brain tumor